2021
DOI: 10.1002/nau.24801
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term lower urinary tract sequelae following AUS cuff erosion

Abstract: To examine the rate of lower urinary tract complications (LUTC) and urinary diversion (UD) after artificial urinary sphincter (AUS) explantation with the acute reconstruction of AUS cuff erosion defects. Methods:We performed a retrospective study of patients who underwent in-situ urethroplasty (ISU) for AUS cuff erosion from June 2007 to December 2020. Outcomes included LUTC (urethral stricture, diverticulum, fistula), AUS reimplantation, and UD. Defect size was prospectively estimated acutely and a subanalysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Given the lack of management guidelines, the available data are mostly based on retrospective studies, in which the management method is dependent on the institutional standardized surgical protocol or is at the surgeon’s discretion. The various management options available in the literature are summarized in Table 1 [ 3 8 ]. It is worth mentioning that in most of the studies the type of AUS was not specified.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the lack of management guidelines, the available data are mostly based on retrospective studies, in which the management method is dependent on the institutional standardized surgical protocol or is at the surgeon’s discretion. The various management options available in the literature are summarized in Table 1 [ 3 8 ]. It is worth mentioning that in most of the studies the type of AUS was not specified.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of patients who developed US after such treatment ranges widely from 8% to 85%. All [ 3 7 ] but one [ 4 ] of the studies involved urinary drainage by transurethral catheter only. Kuhlencord et al noted that their study was the first to propose additional drainage through a suprapubic catheter, and it may be one of the reasons for the very high success rate of conservative treatment without surgical intervention in the urethra [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During device explantation, it is recommended that full explant be performed. Various studies have reported lower urinary tract sequelae after explantation, including an incidence of urethral stricture ranging from 12-61.5% (38)(39)(40)(41)(42). Management of the urethra varies and multiple studies have compared urethral catheter placement, suture urethrorrhaphy (also referred to as abbreviated urethroplasty or in situ urethroplasty), and excisional urethroplasty (primary urethral anastomosis) (38)(39)(40).…”
Section: Bulbar Urethral Compromise Prior Aus Cuff Erosionmentioning
confidence: 99%